1996
DOI: 10.1084/jem.184.4.1279
|View full text |Cite
|
Sign up to set email alerts
|

CD5 is a potential selecting ligand for B cell surface immunoglobulin framework region sequences.

Abstract: SummaryIn rabbits nearly all B lymphocytes express the glycoprotein CD5, in contrast to mice and humans, where only a small proportion of B cells express this molecule (Raman, C., and K.L. Knight. 1992.J. Immunol. 149:3858-3864). CD5 + B cells appear to develop early in ontogeny and be maintained throughout life by self-renewal. The function of CD5 on B cells is still unknown. We showed earlier that "positive" selection occurs during B lymphocyte development in the rabbit appendix. This selection favors B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 33 publications
1
45
1
Order By: Relevance
“…It is also suggested that the regional interaction of surface immunoglobulin with CD5 could provide a autostimulatory signal necessary for B cell survival. 47 This weak but persistent survival signal provided to the B-CLL cell by the continual 'tickling' of CD5 could be disrupted by anti-CD5 MoAbs, which have a higher relative avidity, 44 thus opening the pathway of programmed cell death. Death signals triggered by B cell receptor ligation are dependent on caspase-3, 48 pointing to our finding of caspase-3 involvement in anti-CD5-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that the regional interaction of surface immunoglobulin with CD5 could provide a autostimulatory signal necessary for B cell survival. 47 This weak but persistent survival signal provided to the B-CLL cell by the continual 'tickling' of CD5 could be disrupted by anti-CD5 MoAbs, which have a higher relative avidity, 44 thus opening the pathway of programmed cell death. Death signals triggered by B cell receptor ligation are dependent on caspase-3, 48 pointing to our finding of caspase-3 involvement in anti-CD5-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…44 CD5 was identified to be associated with the human B cell receptor complex 45 and to negatively regulate antigen receptor-mediated signaling. CD5 appears to regulate the early signaling events induced by B cell receptor cross-linking in B-1 cells 46 by setting a threshold which may play a role in protecting cells from antigen receptor firing either spontaneously or by weak cross-reactive interactions with antigens.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanistically distinct role for MuLV in B cell lymphomagenesis could be through chronic low-level stimulation of the B cell receptor, a possibility supported by the observations that NFS.V ϩ lymphomas transplant to virus-positive but not to virus-negative mice (Fredrickson et al, 1985). Essentially all NFS.V ϩ B cell lymphomas express CD5 , and CD5 has been shown to interact with Ig V H framework sequences (Pospisil et al, 1996) as well as CD72 (Luo et al, 1992). Thus, signals provided by MuLV and CD5 could combine to promote B cell survival or proliferation, thus functioning as promoting factors in the evolution of the transformed state.…”
Section: Discussionmentioning
confidence: 99%
“…Several putative endogenous CD5 ligands (CD72, gp35-40, gp150, IgV H framework region, CD5 itself or IL-6) have been proposed by different groups, but these still await independent validation. [20,[29][30][31][32][33]. Moreover, recent studies have shown the ability of CD5 to bind to exogenous microbial structures present on fungi, namely β-glucans, [34] and to viruses, such as hepatitis c virus [35].…”
Section: Cd5mentioning
confidence: 99%